Molecular characterization of breast cancer needle core biopsy specimens by the 21‐gene Breast Recurrence Score test. Issue 4 (4th June 2020) - Jakubowski, Debbie M.; Bailey, Helen; Abran, John; Blacklock, Andrea; Ciau, Nancy; Mies, Carolyn; Tan, Vivian; Young, Rebekah; Lau, Anna; Baehner, Frederick L.
Abstract: Background and Objective: Recent COVID‐19 pandemic guidelines recommend genomic assessment of core biopsies to help guide treatment decisions in estrogen receptor (ER)‐positive early‐stage breast cancer. Herein we characterize biopsy and excisional breast cancer specimens submitted for 21‐gene testing. Methods: US samples submitted to Genomic Health for 21‐gene testing (01/2004‐04/2020) were assessed by pathologists and analyzed by a standardized quantitative reverse transcription‐polymerase chain reaction. Predefined cutoffs were: ESR1 (positive ≥6.5), PGR (positive ≥5.5), and ERBB2 (negative <10.7). ER status by immunohistochemistry (IHC) and lymph node status were determined locally. Median and interquartile range were reported for continuous variables, and total and percent for categorical variables. Distributions were assessed overall, by age, and by nodal involvement. Results: Of 919 701 samples analyzed, 13% were biopsies and 87% were excisions. Initial assay success rates were 94.5% (biopsies) and 97.3% (excisions). ER IHC concordance with central ESR1 was 96.8% (biopsies) and 97.6% (excisions). Biopsy and excisional medians were: Recurrence Score results 16 (each); ESR1 10.2 (each); PGR 7.7 and 7.6; ERBB2 9.4 and 9.2, respectively. Conclusions: Biopsy submissions for 21‐gene testing are common and consistently generate results that are very similar to the experience with excisions. The 21‐gene test can be performed reliably on core biopsies.